Jakobson's First Post-War Visit to Czechoslovakia in 1957 in Light of the Archives of the State Security - Dittmann, Robert (Bohemica Olomucensia, 2017)
The contribution focuses on Roman Jakobson's first post-World War II visit to Czechoslovakia he luckily left in April 1939. The regime changed from the Nazi Protectorate to the Communist dictatorship. The article describes how he was closely followed by the Czechoslovak security services and suspected of being an agent of the intelligence service of the USA. The extensive materials gathered by the Czechoslovak authorities have been stored in the Archives of Security Services in Prague, Czech Republic.
Keywords: Roman Jakobson; Czechoslovakia; State Security